If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -12 + 59 = 4x + 20 Reorder the terms: -12 + 59 + 3x = 4x + 20 Combine like terms: -12 + 59 = 47 47 + 3x = 4x + 20 Reorder the terms: 47 + 3x = 20 + 4x Solving 47 + 3x = 20 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 47 + 3x + -4x = 20 + 4x + -4x Combine like terms: 3x + -4x = -1x 47 + -1x = 20 + 4x + -4x Combine like terms: 4x + -4x = 0 47 + -1x = 20 + 0 47 + -1x = 20 Add '-47' to each side of the equation. 47 + -47 + -1x = 20 + -47 Combine like terms: 47 + -47 = 0 0 + -1x = 20 + -47 -1x = 20 + -47 Combine like terms: 20 + -47 = -27 -1x = -27 Divide each side by '-1'. x = 27 Simplifying x = 27
| 1.75x+0.75=4.75 | | 75x+255=1605 | | -4(6n-1)=100 | | 32+-4x=18+-2x | | 4(y-8)=-20 | | -y/5-2-0 | | -3(4x-6)=90 | | (5x+1)+19=(18x-6) | | 33x+78=200 | | (2x-7/x=4)=3 | | s=32t-16t^2 | | -3b+7(-b-4)=-88 | | 0.1p-0.2p=-6.6 | | -6n-2=22 | | 5x+48y+50=180 | | 12+(5x+1)=(18x-6) | | 98=-6-8n | | 55.50x+400=2000 | | 12+(5x+1)=((9x-3)*2) | | 7.00h+2.00h=58.50 | | x^2-2x-7=2cosx | | 5=2x+b+4 | | (5x+1)+19=(9x-3) | | 5+3-8+4+x=7 | | 18=8+5u | | 3x-5(x-5)=-3+4x+10 | | 24=m+60 | | -5.46+x=-.3 | | -4(3x+7)=-76 | | x^2-4x-7=3cosx | | 196x=196 | | 7x/3=35 |